2020
DOI: 10.1016/j.jpainsymman.2019.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Specialized Pediatric Palliative Care: A Systematic Review

Abstract: Context: Specialized pediatric palliative care (SPPC) is increasingly involved in the care of seriously ill children, yet the evidence on its impact has not been comprehensively reviewed.Objective: To assess the effects of providing SPPC to seriously ill children on patient-, caregiver-, and systems-level outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 69 publications
0
51
0
2
Order By: Relevance
“…Our finding that end-of-life care is different for those who receive specialist paediatric palliative care compared to those who do not broadly aligns with three recent reviews about children with all life-limiting conditions. 19,28,29 Two of these reviews 19,29 concluded that specialist intervention appears to offer benefit in terms of improved quality of life. By focusing only on children and young people with cancer, our review highlights the lack of robust evidence pertaining to both quality of life and symptom burden in this population.…”
Section: What This Review Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that end-of-life care is different for those who receive specialist paediatric palliative care compared to those who do not broadly aligns with three recent reviews about children with all life-limiting conditions. 19,28,29 Two of these reviews 19,29 concluded that specialist intervention appears to offer benefit in terms of improved quality of life. By focusing only on children and young people with cancer, our review highlights the lack of robust evidence pertaining to both quality of life and symptom burden in this population.…”
Section: What This Review Addsmentioning
confidence: 99%
“…26,27 Recent systematic reviews suggest that access to specialist palliative care services is associated with improvements in quality of life, symptom control, perceived support, reduced time in hospital, less invasive treatment and greater advance care planning. 19,28,29 However, these reviews have aggregated the results for children and young people across conditions, and the evidence for those with cancer remains unclear because of conflicting results between individual studies 28 and the lack of work exploring condition-specific factors that may influence access to and benefit from specialist palliative care services. 30,31 A rigorous review of the evidence on the impacts of specialist paediatric palliative care for children and young people with cancer and their families is both crucial to informing debates within paediatric oncology regarding the positioning and role of these specialist services and for future service development.…”
Section: Introductionmentioning
confidence: 99%
“…Issues related to race/ethnicity, gender, religion, immigrant status, education level, socioeconomic status, sexual orientation, and indigenous heritage are just a few of the cultural factors that can impact treatment and the experience of care 22–24 . Furthermore, these factors may also play a part in how AYAs and their families view illness, death, the medical system, and decisions 25,26 about the care provided at EOL 27,28 . Developmentally, it is appropriate for AYAs to start exploring what values and belief systems are important to them, which may differ from those of their family of origin.…”
Section: Diversity and Cultural Considerationsmentioning
confidence: 99%
“…For many patients and families, being given the choice to plan is just as important as the location itself. AYA patients most often prioritize their relationships with others when making EOL decisions, in addition to directing their medical treatment, defining their care plans, the information their family and friends receive, and how they wish to be remembered 5–57,59–61 . Parents of critically ill children who planned the location of death achieved a home death 72% of the time compared to only 8% of those who did not plan 46 .…”
Section: Location Of End‐of‐life Carementioning
confidence: 99%
“…Palliative care can play an important role for children and young people with lifelimiting conditions (LLC), enhancing quality of life for children and their families. [1][2][3] In England it is estimated that more than 86,000 children and young people have a life-limiting or life-threatening condition (2017/18). 4 These include diseases without a cure which result in early death (e.g.…”
Section: Introductionmentioning
confidence: 99%